Platform-dependent entrepreneurship: A systematic review - Songping Yu; Tomoki Sekiguchi (Administrative Sciences, 2024)
Digital platforms have facilitated the emergence of novel entrepreneurial opportunities that rely on a platform for market entry and access to resources. This systematic review synthesizes current knowledge on how platforms impact and shape "platform-dependent entrepreneurship" and how platform-dependent entrepreneurs (PDEs) respond to power asymmetries. The results of the review suggest that platforms lower barriers to entry but also lead to PDEs' dependence and precarity. Specifically, platform governance significantly impacts PDEs' behavior by shaping their market access, visibility, and opportunities through various mechanisms. In response, PDEs employ several strategies to preserve their autonomy, such as engaging in multi-homing, capitalizing on branding, and conducting activities outside of the platform. Thus, PDEs' entrepreneurial identity is co-constructed through the interplay of individual agencies and platform dynamics as they navigate tensions in the platform ecosystem. Based on this review, we present a research agenda for the future that has substantial implications for the theory and application of PDEs in the literature.
Keywords: 350; platform-dependent entrepreneurship; systematic integrative review; power-dependence theory